2020
DOI: 10.1101/2020.12.04.411751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Binary Relations for Ontology Extension and Improved Adaptation to Clinical Text

Abstract: BackgroundThe controlled domain vocabularies provided by ontologies make them an indispensable tool for text mining. Ontologies also include semantic features in the form of taxonomy and axioms, which make annotated entities in text corpora useful for semantic analysis. Extending those semantic features may improve performance for characterisation and analytic tasks. Ontology learning techniques have previously been explored for novel ontology construction from text, though most recent approaches have focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For example, the current measure of information content is weighted by the frequency the concept appears in the corpus, however these can also be calculated topologically, on the basis of how general or specific the classes are [24]. Our previous work has also demonstrated that expansion of vocabulary [25] and ontology extension [26] can improve performance of a similar tasks. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [27], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the current measure of information content is weighted by the frequency the concept appears in the corpus, however these can also be calculated topologically, on the basis of how general or specific the classes are [24]. Our previous work has also demonstrated that expansion of vocabulary [25] and ontology extension [26] can improve performance of a similar tasks. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [27], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [28].…”
Section: Resultsmentioning
confidence: 99%
“…Other work has also focused on ontology extension through text, which may also improve performance of semantic similarity tasks [25]. Our previous work also showed that extension of ontologies by examining binary relations mined from text, and extension of ontology vocabularies with information from other ontologies, improved performance at a semantic similarity-based patient characterisation tasks [26, 27]. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [28], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other work has also focused on ontology extension through text, which may also improve performance of semantic similarity tasks [ 1 ]. Our previous work also showed that extension of ontologies by examining binary relations mined from text, and extension of ontology vocabularies with information from other ontologies, improved performance at a semantic similarity-based patient characterisation tasks [ 24 , 26 ]. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [ 27 ], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [ 14 ].…”
Section: Discussionmentioning
confidence: 99%